Assessment of the effect of agro-industrial by-products rich in polyphenols on in vitro fermentation and methane reduction in sheep - Vastolo, Alessandro; Mora, Blandine; Kiatti, Dieu donné; Nocerino, Martina; Haroutounian, Serkos; Baka, Rania D.; Ligda, Panagiota; Cutrignelli, Monica Isabella; Niderkorn, Vincent; Calabrò, Serena (Frontiers in Veterinary Science, 2025)
IntroductionThis study aimed to evaluate, using the in vitro gas production technique, the effect of including eight agro-industrial by-products (carob, grape, two types of olive pomace, citrus pulp, tomato, and hazelnut skin) on fermentation end-products, ruminal degradability, and methane production in sheep diets.MethodsThe by-products were included at 10% dry matter in the control (CTR) diet, commonly adopted for adult sheep (80% natural grassland and 20% concentrate), and incubated at 39°C under anaerobic conditions.Result and discussionAfter 24 h of the incubation, the organic matter degradability (OMD24h) and methane production were assessed. After 120 h of the incubation, the organic matter degradability (OMD120h), volume of gas produced (OMCV), fermentation kinetics, pH, volatile fatty acids (VFAs), and ammonia were evaluated. Dunnett’s test was used to compare the differences between the control and experimental diets, and multivariate analysis was performed to highlight the differences among the diets based on their in vitro characteristics. The results indicated that the inclusion of the by-products decreased the degradability and increased gas production after 120 h of the incubation. The by-products from the hazelnuts, citrus, grapes, and tomatoes significantly (p < 0.001) reduced the methane production, whereas the pomegranate, grape, 3-phase olive cake, tomato, and hazelnut by-products significantly (p < 0.001) increased the acetate production. The multivariate analysis showed that the butyrate concentration was a determining factor in the differences between the diets. The concentration of polyphenols in the selected agro-industrial by-products could modify fermentation parameters and metabolic pathways, leading to reduced methane production.